Pengaruh Manajemen Pendidikan Budaya dan Karakter Pendidikan Di Sekolah Dasar Negeri 114 Palembang - Nyimas Atika (El-Idare, 2017)
One of the latest national education policies in Indonesia is to carry out character education of the nation's values in school schools in Indonesia. In the process of cultural education and character of the nation, the students actively develop their own potential, internalize the process, and appreciate the values into their personalities in socializing, developing a more prosperous society, and developing the life of a dignified nation. Culture is the whole system of ideas and feelings, actions, and the work that humans produce in the life of society that is owned by him by way of learning. Through education that develops the cultural values and character of the nation, learners have value and character as their character, able to apply these values in life as members of society and citizens who are religious, nationalist, productive and creative.